The Effect of an Educational Intervention on Obstetrics and Gynecology Residents' Postpartum Depression Knowledge [A45]. (May 2022) - Haslam, Melissa D.; Cruz, Amy; Baweja, Ritika
Abstract : INTRODUCTION: Up to 15% of women experience postpartum depression (PPD), and maternal suicide is a leading cause of maternal mortality. Obstetrician-gynecologists (ob-gyns) are intimately involved in postpartum care of women and are in a position to help diagnose and manage PPD. Council on Resident Education in Obstetrics and Gynecology (CREOG) learning objectives include goals for residents to diagnose and perform initial management of postpartum complications such as PPD. The objective of this study was to assess if a psychiatry educational intervention (pre-recorded didactic lecture and facilitated discussion) would improve ob-gyn residents' knowledge and comfort level in diagnosing and managing PPD. METHODS: We performed an educational intervention study including ob-gyn residents at an academic training program. A pre-lecture survey/test was sent to residents. A prerecorded psychiatric didactic session was sent to residents. Participants were instructed to complete the post-lecture survey/test. A facilitated discussion via Zoom at which time presubmitted questions were reviewed and discussed with a psychiatrist was performed. A postdiscussion survey was then sent out. RESULTS: Before the intervention, 32% of residents agreed/strongly agreed that they felt comfortable diagnosing PPD; after the intervention, this increased to 81% of residents. Before the intervention, 25% of residents agreed/strongly agreed that they felt comfortable treating PPD; after the lecture/discussion this increased to 69% of residents. The difference in pre and post test scores was significantly improved (POST-PRE difference of 2.6 with a 95% CI of 1.8-3.5, P <.0001). CONCLUSION: This study helps show the importance of interdisciplinary didactics and interactive learning sessions which can help improve ob-gyn residents' knowledge and comfort level in diagnosing/managing PPD in patients.